Anatomy of a rape: sexual violence and secondary victimization scripts in U.S. film and television, 1959-2019 - Hogan, Jackie (Crime, media, culture, 2022)
The rape law reform movement in the U.S. has made significant progress since the 1970s. All fifty U.S. states and the District of Columbia have now made changes to their rape statutes. Nonetheless, the incidence of reported rape has increased substantially since the 1970s, and rape conviction rates have remained frustratingly low. Such statistical evidence suggests that amending legal statutes has not proven sufficient to curb endemic sexual violence in the U.S. Effective prevention requires a deeper understanding of rape culture, the conglomeration of discourses, ideologies, and practices that normalize sexual assault. Of particular interest here are mass mediated representations of rape, and their power to authorize or critique sexual violence, its root causes, and its consequences. This paper interrogates and seeks to disrupt rape culture by critically analyzing three media texts with narratives based on real-world cases of sexual violence and secondary victimization, the films Anatomy of a Murder, 1959 and The Accused, 1988 and the Netflix miniseries Unbelievable, 2019. With roughly thirty years between these texts, they provide snapshots of shifting attitudes and practices around sexual violence and secondary victimization in the U.S., from the pre-reform era to the #MeToo era. The analysis reveals some heartening changes but also some disturbing continuities in the real-world ideas and practices that media texts reflect and amplify.